2023
DOI: 10.1007/s42452-023-05371-2
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of aquifer promising zones and protective capacity for regional groundwater development and sustainability

Abstract: Water security is the central mission of the sustainable development goals. The demand for potable and clean water has skyrocketed due to frequent borehole failures and population expansion, which requires adequate groundwater resource management strategies. Identifying groundwater potential zone, overburden protective index capacity and installations of alternative/artificial storage support mechanisms for water security and sustainability under the growing water challenge and demand is critical. This study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…According to [64,55], the resistivity of a fresh basement is a function of its degree of weathering, the fresh basement having resistivities ranging from 1030 Ωm to 9109 Ωm, shows that some parts of the study area are weathered and fractured having resistivity lower less than 1500 Ωm, and this could indicate high aquifer potentials strength. This is because, [64,55] observed that when an area has low basement resistivity values (< 2000 Ωm) is an indication that, the region may have probably been faulted, fractured, or heavily weathered, which could be of great interest to the development of groundwater potential. Interestingly, the low resistivity of the weathered/fractured layer with a high thickness indicates high groundwater potential.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to [64,55], the resistivity of a fresh basement is a function of its degree of weathering, the fresh basement having resistivities ranging from 1030 Ωm to 9109 Ωm, shows that some parts of the study area are weathered and fractured having resistivity lower less than 1500 Ωm, and this could indicate high aquifer potentials strength. This is because, [64,55] observed that when an area has low basement resistivity values (< 2000 Ωm) is an indication that, the region may have probably been faulted, fractured, or heavily weathered, which could be of great interest to the development of groundwater potential. Interestingly, the low resistivity of the weathered/fractured layer with a high thickness indicates high groundwater potential.…”
Section: Resultsmentioning
confidence: 99%
“…That is, the high and values usually indicate relatively high thick succession layers and it should be the focus in terms of groundwater potential [49,50,51,52,53,54]. On the other hand, [5,55], noted that the earth most times acts as a natural lter to the in ltrating uid, especially when the earth's subsurface is underlain with an indurated laterite and impermeable clayey, which in turn de nes its ability to resist uid and the degree of its protective capacity [1]. Consequently, the aquifer protective capacity can evaluate from Dar-zarrouk parameters, ( and ), [1,4,56], as:…”
Section: Soil Conductivitymentioning
confidence: 99%
“…Geophysical methods are implemented in a wide range of applications ranging from magnetic, gravity, seismic, electrical resistivity, electromagnetic, induced polarization, radioactive, and so on [4]. However, electrical resistivity surveys remain one of the most efficient and suitable methods for groundwater exploration, especially for depth information [11,12,13]. However, many configurations of electrodes have been designed for electrical resistivity surveys (Vertical electrical sounding), which are occasionally employed in specialized surveys such as mineral and groundwater exploration [7,14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Groundwater is a hidden natural resource and it is very vital to human existence due to its roles in all aspects of life. Frequent borehole failure according to several sources is attributed to the fact that most boreholes and hand-dug wells were not sunk based on good hydrogeological/geophysical information, but are drilled at locations pre-determined by their owners [1,2,3]. Some remarkable studies observed that the roles of groundwater in nation-building cannot be overemphasized [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…According to [3], more than 30% of the boreholes dug within the complex basement reportedly failed, while the so-called successes were not encouraging due to low yield. In addition, a remarkable study noted that to ensure adequate water security and sustainability, there is a need to install multiple boreholes in geophysical identi ed groundwater promising zones where the aquifer occurs in deeper zones and fractured [3]. This is because most remarkable studies conducted in the complex basement rock noted that the weathered/fractured units are largely responsible for the regional groundwater-bearing capacity [3,11,17,18]These situations therefore make this type of investigation a prima facie for the precise location of fractured zones for productive borehole sites.…”
Section: Introductionmentioning
confidence: 99%